Desenvolvimento de ferrita de cobalto (CoFe2O4) para aplicações em dispositivos de micro-ondas - Silva, Pedro Bruno Nogueira da (2020)
The constant progress in communication technologies demands greater capabilities in your systems in addition to comfort. Some researches related to improvements in communication devices is largely realized because of this demand. These researches can be made in the structural form of the devices or simply in their material composition. This work aims to evaluate the feasibility of the material Cobalt Ferrite (CoFe2O4) for composition of a resonator in a dielectric resonator antenna (DRA), or ferrimagnetic resonator antenna (FRA), and for the composition of a substrate in microstrip antenna. The proposed material was produced by the Sol-Gel method. The electromagnetic characterization of the material was executed, as well as simulations in the ANSYS HFSS® software and measurements of its reflection parameters by using a Vector Network Analyzer. The built-in antennas showed satisfactory results, mainly in DRA application, with a return loss of -48.52 dB and an input impedance of 50.134 - j 0.055 Ω at the resonance frequency of 7.31 GHz